Comparison of Sn and as Effect on Tensile Properties of Pb–3.5%Sb Grid Alloy for Lead-Acid Batteries - Dzenzerskiy , Victor O.; Tarasov, Serhii V.; Sukhova, Olena V.; Ivanov, Volodymyr A. (East European Journal of Physics, 2026)
In this work, the effects of 0.5 wt.% Sn and 0.16–0.23 wt.% As on tensile properties of Pb–3.5%Sb grid alloy for lead-acid batteries were compared in the as-cast condition. The alloys were melted under different cooling-rate conditions in a casting mold preheated between 50°C and 170°C, with cooling rates ranging from 100 °C/s to 50 °C/s. Mechanical properties, such as ultimate tensile strength and percentage elongation, were measured at room temperature using the TIRAtest 2300 universal testing machine at a constant crosshead speed of 10 mm/min. It was established that as mold preheating temperatures rise, the elongation and ultimate tensile strength of the Pb–3.5%Sb–0.23%As alloy decrease by 13.9% and 11.8%, respectively. Addition of tin in place of some arsenic causes a decrease in ultimate tensile strength of the Pb–3.5%Sb–0.5%Sn–0.16%As alloy, but only by 2.8 %, whereas elongation increases by 2.4 %. It was concluded that additions of tin compensate for the negative effect of arsenic on the tensile properties of the Pb–3.5%Sb grid alloy, which relates to the formation of brittle arsenic-containing phases at the grain boundaries. Tin addition to the Pb–3.5 %Sb alloy produces higher tensile properties at room temperature than those obtained by the addition of arsenic.